Pains and delights in learning: leisure and work in university training in Dance - Müller Pinto, Renato; Barbosa Pereira, Alexandre (Argumentos - Revista do Departamento de Ciências Sociais da Unimontes, 2023)
Based on an ethnography that accompanies the learning processes in an undergraduate dance course, this article intends to explore the different ways in which the understanding of leisure and work appears. Admitting that the formation of the Dance artist is not limited to the university path, the article intends to analyze how leisure participates in the formation of these artists. Thus, beyond this formal context of learning Dance, it is intended to address the way in which students, in their leisure activities, refine their sensibilities.